Nanomechanics of Extracellular Vesicles Reveals Vesiculation Pathways. Issue 39 (30th August 2018) - Sorkin, Raya; Huisjes, Rick; Bošković, Filip; Vorselen, Daan; Pignatelli, Silvia; Ofir‐Birin, Yifat; Freitas Leal, Joames K.; Schiller, Jürgen; Mullick, Debakshi; Roos, Wouter H.; Bosman, Giel; Regev‐Rudzki, Neta; et al.
Abstract: Extracellular vesicles (EVs) are emerging as important mediators of cell–cell communication as well as potential disease biomarkers and drug delivery vehicles. However, the mechanical properties of these vesicles are largely unknown, and processes leading to microvesicle‐shedding from the plasma membrane are not well understood. Here an in depth atomic force microscopy force spectroscopy study of the mechanical properties of natural EVs is presented. It is found that several natural vesicles of different origin have a different composition of lipids and proteins, but similar mechanical properties. However, vesicles generated by red blood cells (RBC) at different temperatures/incubation times are different mechanically. Quantifying the lipid content of EVs reveals that their stiffness decreases with the increase in their protein/lipid ratio. Further, by maintaining RBC at "extreme" nonphysiological conditions, the cells are pushed to utilize different vesicle generation pathways. It is found that RBCs can generate protein‐rich soft vesicles, possibly driven by protein aggregation, and low membrane–protein content stiff vesicles, likely driven by cytoskeleton‐induced buckling. Since similar cortical cytoskeleton to that of the RBC exists on the membranes of most mammalian cells, our findings help advancing the understanding of the fundamental process of vesicle generation. Abstract : A detailed atomic force microscopy force‐spectroscopy study of natural vesicles reveals that the bending modulus of membranes of extracellular vesicles decreases as their total protein content increases. Generation of protein‐rich soft vesicles by red blood cells is possibly driven by protein aggregation, while the generation of low membrane–protein content stiff vesicles is likely driven by cytoskeleton‐induced buckling.